Strategi MI PK Al Islam Pucangsawit dalam Memetakan Kemampuan Awal Peserta Didik melalui Asesmen Diagnostik pada PPDB - Agus Triyono; Achmad Rasyid Ridha (Lembaga Yasin AlSys, 2026)
Mapping students’ initial abilities during the New Student Admissions (PPDB) process is necessary to support instructional planning that meets individual needs, but its implementation through diagnostic assessment at the Islamic elementary school level remains underexplored. This study aimed to describe the strategy employed by MI PK Al Islam Pucangsawit to map students’ initial abilities through diagnostic assessment during the PPDB process. The study employed a descriptive qualitative approach with a field research design. Data were collected through observations, interviews, and documentation involving the head of the madrasah, teachers, the PPDB committee, and students’ parents as research participants. The results showed that the diagnostic assessment was implemented systematically and covered academic abilities in reading, writing, and arithmetic; religious abilities in reading Iqro’ and recognizing Arabic letters; and students’ learning and social readiness. The assessment was conducted individually using a child-friendly approach, thereby providing a more accurate description of students’ initial conditions. The assessment results were subsequently used as a basis for class grouping, the development of assistance programs, and differentiated learning planning. This study concludes that diagnostic assessment during the PPDB process is an effective strategy for mapping students’ initial abilities and supporting improvements in the quality of instructional planning and implementation at the madrasah.